Civilizational clash or co-existence: an Islamic perspective - Osmani, Noor Mohammad (Islamic Research Institute for Culture and Thought in the Islamic Republic of Iran, 2009)
Right after the Cold-War a lopsided dominance of the Western civilization took a shape in reality, creating an invisible division of the West and the rest. This imaginary division, in affect, triggered a cultural domination of the Western culture and traditions, undermining other cultures. Hence there took a turnabout in history from a ‘physio-psychical’ war to a ‘psycho-cultural’ war. Huntington argued that there will be seven – eight civilizations ruling the next century, thus resulting to a possible clash among them. And among these, West faces the greatest threats from the Islamic civilization. The purpose of this research is to examine the perceived clash between civilizations and the criteria that lead a civilization to precede others from both Islamic and Western perspective. The research would conduct a thorough study of the available literatures, analyze historical facts and data and make a critical evaluation.On the basis of the criteria for civilizational hegemony from an Islamic view point,this paper argues that there should be no clash, rather a co-existence of civilizations.